The sources of aggregate profitability: Marx's theory of surplus value revisited - Peter Flaschel; Nils Fröhlich; Roberto Veneziani (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2013)
This paper provides an empirical analysis of Marx's theory of exploitation built on the standard interpretation of the value of labour power. The relationship between the aggregate value rate of profit and the aggregate price rate of profit is studied and it is shown that the two rates coincide up to negligible deviations by using flow as well as stock matrix data for the German economy (1991–2000). This suggests that the main determinants of the value rate – namely absolute and relative surplus value, as well as technical progress affecting the value of the aggregate capital stock – may help to understand the dynamics of the aggregate market rate of profit.
Keywords: B51; C67; D46; D57; 330; labour values; profit rates; input–output models